The Sosio-Economic Impact of Covid-19 Pandemic in Lhokseumawe City - Angga Syahputra; Mukhtasar Mukhtasar (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2020)
AbstractIn the midst of government preventive efforts to implement health protocols, public activities of the Lhokseumawe City are still running normally. Whereas based on theory and former studies, the outbreak of Covid-19 caused social and economic changes has affected activities of people around the world. Using descriptive qualitative method, this study aims to analyze how the impact of local government policies to the socio-economy activities of the Lhokseumawe people and what factors influenced the response of Acehnese in the pandemic situation. Data were obtained through interview, observation to the public area, and library research on the impact of the pandemic to the society. It examines that Lhokseumawe City government policies such as imposing curfews, prohibiting gatherings in Cafe and social distancing have received less response from the public. Community activities in trading, worshiping and social interaction tend not to be affected by information on the highly spreading of Covid-19 in this city. However, school and office activities relatively follow Central Government policies. The response of the Lhokseumawe people is based on their belief that the virus is a creation of God and the pandemic situation reminds them to further increase their worship and not to be afraid to carry out normal activities. Even if they die, it is part of their destiny. Thus, the results of the study provide support for local governments to increase cooperation with Ulama in providing education to the public, increasing literacy for the spread of Covid-19, and the possibility of applying legal sanctions.